MECHANO-MATHEMATICAL MODEL AND EXPERIMENTAL RESULTS ON THE DYNAMIC RELATION BETWEEN MARINE PROPELLER OSCILLATION AND MAIN SHIP ENGINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Ship propellers, essential for propulsion, can cause unwanted hull vibrations. These vibrations affect crew comfort, increase maintenance costs, and potentially reduce fuel efficiency. This study addresses this issue with a novel mechano-mathematical model that analyses the propeller contribution to vibrations. Previous models have focused primarily on the engine as the vibration source. This work bridges the gap by considering the dynamic interplay between different vibration modes within the entire propulsion system: engine, shaft line and propeller. It considers key elements such as engine torque variations, propeller moment and system elasticity. The model represents these components with the propeller as a weightless elastic element. It meticulously accounts for the complex motion of the propeller, allowing its absolute speed to be calculated. The model recognises the flexibility of the shaft line and represents the engine using simplified point masses based on established principles. A reference system tracks the position of each component, capturing engine vibration, stern tube bearing motion and shaft line torsional stiffness. A set of differential equations governs the oscillations of the system, incorporating relevant factors such as engine inertia and torque, propeller moment, and inertial and hydrodynamic forces. The model captures the dynamic relationship between different modes of vibration, including propeller, engine, shaft precession and torsional vibrations from both engine and propeller. While detailed equations and experimental results are omitted, a qualitative analysis demonstrates the model's ability to predict the frequencies of real-world vibration spectra. This successful validation highlights its potential to capture propeller-induced vibration dynamics. By pinpointing excitation mechanisms with greater accuracy, this research can pave the way for improved propeller designs that minimise vibration, leading to improved crew comfort, reduced maintenance costs and potentially even improved fuel efficiency.